The “Document of German Art” Exhibition (1901) in the Context of the Opening of the Darmstadt Colony: Gesamtkunstwerk or Synthesis of Arts? - Grigorash, Alyona V. (Actual Problems of Theory and History of Art, 2025)
Examining the program texts written by the members of artists’ Colony in connection with the exhibition “Document of German art”, the author provides detailed analysis of the buildings created at Darmstadt under the influence of the arts interaction idea. On the basis of differential approach to the usage of notions ‘Gesamtkunstwerk’ and ‘synthesis of arts’ the author proposes a hypothesis that ‘Gesamtkunstwerk’ is manifested in a private estate house, while the phenomenon of the ‘Synthesis of arts’ more relates to the exhibition practice, whereof Darmstadt Colony exhibition of 1901 is a bright example.
Keywords: Darmstadt artists сolony; Jugendstil; synthesis of arts; Gesamtkunstwerk; J. M. Olbrich